Analysis of the Calculation Value of Domestik Component Level (TKDN) on high-rise building projects - Ningtyas, Diah Kurniawati; Pahang Putra, I Nyoman Dita (Program Studi Teknik mesin, Fakultas Teknik, Universitas Al Azhar Medan, 2024)
Domestic products can be used to increase productivity and competitiveness in international markets. The government stipulates the use of domestic products by setting the sum of the value of the domestic component level and the weight of company benefits at 40%. Until now, there has not been much use of domestic products in the construction sector. Therefore, this study considers the value of the domestic component level in high-rise building projects to strengthen Indonesia's competitiveness in the industrial sector. In this study, the calculation method and value of the domestic component level will be analyzed along with the weight of benefits of construction service companies for multi-story building construction projects. The technique used in this study is quantitative, and it processes data such as technical specifications, cost budget plans, unit price analysis of work, and finding the percentage level of domestic material components through the Ministry of Industry website. The result obtained by this study is the percentage value of the domestic component level (TKDN) in high-rise building projects is 74.53%, the percentage value of the company's benefit weight is 3%, and the total value of TKDN and BMP is 77.53%. The conclusion obtained in this study is that the high-rise building project has met the requirements in the Presidential Regulation of the Republic of Indonesia Number 12 of 2021 concerning the Procurement of Goods and Services.